Implementasi Model Scamper sebagai Strategi Asimilasi Perwajahan Typeface “Antawacana” Bercitra Wayang Golek Sunda - Yunianto, Ipung Kurniawan; Priliuno, Syaima (Institut Seni Indoensia Surakarta, 2023)
The earliest modes of human communication were gestures and symbols, which eventually evolved into letters and fonts that are crucial for facilitating everyday activities. Font design (typeface) development reflects the current cultural zeitgeist and allows traditional elements to be incorporated as visually relevant elements in modern situations, one of which is the Sundanese Wayang Golek possesses anatomical characteristics that resemble those of humans, making it possible to adapt them as a typeface element and incorporate them into visual designs. This study employs a technique that blends anatomical elements of fonts and Sundanese Wayang Golek, to discuss the innovation of decorative typeface design, utilizing the SCAMPER model approach as a brainstorming method. The approach was initially introduced by Alex Osborne in 1953 and later developed by Bob Eberle in 1971. The typeface design outcomes are expected to reflect the representation of Sundanese Wayang Golek, by following the typographical principle. This research's significance is that it offers a strategic and creative approach to introducing Sundanese culture through typefaces